Kepemilikan Paten Spare Part Magic RingStudi Tentang Kontruksi Hukum Dalam Perjanjian AntaraCV.Indosumitech Dengan Investor Di Boyolali(Studi kasus paten produk penghemat bahan bakar motor Magic Ring) - Diastika, Sherviana, Kelik Wardiono, S.H., M.H (2016)
Sherviana Diastika. NIM. C.100.100.130. Kepemilikan paten spare part Magic Ring studi tentang kontruksi hukum dalam perjanjian antara CV.Indosumitech dengan Investor di Boyolali. Fakultas Hukum Universitas Muhammadiyah Surakarta. 2016. This research is a normative juridical research , namely the construction of the law of partnership agreements between inventors and investors in CV.Indosumitech . source data using secondary data in the form of patent laws . Data were analyzed using qualitative analysis . The results showed that : 1 ) the legal construction of a cooperation agreement between the Investor Inventor is a cooperation agreement communion . This is in accordance with article 1618 and 1619 of the Civil Code and opinions J.Satrio ; 2 ) legal protection for Inventor if investors do defaults in partnership cooperation agreement : first the joint venture will terminate and reclaim the patent certificate as collateral in the agreement , as well as return the product that has been manufactured . This is in accordance with article 1619 of the Civil Code and opinions J.Satrio . Keywords : Agreement , Guild , Default .